Levels of Intertextuality in the Novel Na’ib Azrael by Yusuf al-Sibai - bensalah, dhekra (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:32c27e8d-0406-4310-8c57-7cfb6e3aa634-54" data-testid="conversation-turn-110" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="b947097d-6840-4308-8c17-a4c35669560c" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> In this article, we aim to uncover the levels of intertextuality present in the studied novel. We begin by providing a definition of the term on which our study is based. In the following section, we examine the manifestations of religious and literary intertextuality within the novel, exploring the author’s intentions behind them.